Resource allocation in the Grid. A market engineering approach (2007)
The Grid provides access to distributed computational capabilities such as processors or storage space. One of the key problems is deciding which jobs are to be allocated to which resources at what time. In this context, the use of market mechanisms is a promising approach to solve these problems. This book proposes an auction mechanism for allocating computer resources which have multiple quality attributes and time constraints.The auction is evaluated by means of a numerical simulation.